2007
DOI: 10.1103/physrevb.75.014511
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-state purification protocols for a Cooper pair box

Abstract: We propose techniques for implementing two different rapid-state purification schemes, within the constraints present in a superconducting charge qubit system. Both schemes use a continuous measurement of charge ͑z͒ measurements and seek to minimize the time required to purify the conditional state. Our methods are designed to make the purification process relatively insensitive to rotations about the x-axis, due to the Josephson tunneling Hamiltonian. The first proposed method, based on the scheme of Jacobs ͓… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…This paper was prompted by the absence of such arguments in the current physics literature (but see [8]). In particular, we have verified the optimality of previously proposed control strategies for two problems of current interest [1,2,3,20,21,22] in nonlinear quantum feedback control.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This paper was prompted by the absence of such arguments in the current physics literature (but see [8]). In particular, we have verified the optimality of previously proposed control strategies for two problems of current interest [1,2,3,20,21,22] in nonlinear quantum feedback control.…”
Section: Discussionmentioning
confidence: 81%
“…Various strategies with finite controls were investigated numerically for a particular (solid-state) setting in Ref. [21], with no claims of optimality.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies on rapid purification showed that the proposed protocol was optimal, in that it maximized the average rate of purification, but it did not minimize the time taken to reach a given level of purity [15]. Other work has generalized these results for different optimization conditions [16], N-level systems [17], practical implementation of the controls [18], shared entangled states [19], imperfections [20], inefficient detection [21], and mixed protocols [21,22]. In particular, Li et al demonstrated that when the efficiency of the detector is lower than 50%, there is no predicted speed up in purification rate [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that it is possible to increase the speed at which a measurement purifies the state of a quantum system by using real-time feedback control as the measurement proceeds [1,2,3,4,5,6,7,8,9]. Specifically, by using feedback to keep the state of the system diagonal in a basis that is unbiased with respect to the measured observable, one can make the system purity increase deterministically at a rate faster than the increase of the average purity by measurement alone [1,2].…”
mentioning
confidence: 99%